Age estimation by the spheno-occipital synchondrosis assessment through computed tomography scan / Mohamad Furqan Bahari and Shahridah Kassim - Kassim, Shahridah; Bahari, Mohamad Furqan (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Age estimation is a process where chronological age of a person is estimated by studying the age of their bones or teeth. Careful selection of the bones used in the study is important to achieve a close accurate age estimation of a person. The aim of this study was to investigate the relationship between the spheno occipital synchondrosis (SOS) and age for the Malaysian population. The relationship is further studied by determining the correlation of the Malaysian SOS with age for each gender using two different methods. A total of 166 Computed Tomography (CT) Head images 1 mm (male, n = 84, female, n = 82) were collected at the Department of Radiology, Hospital Universiti Sains Malaysia (HUSM). The SOS in the 166 CT images was analysed using qualitative and quantitative approach. The qualitative analysis was done by staging the synchondrosis fusion state into four stages and the fusion state is assessed by a radiologist. The quantitative analysis was done by recording the mean Hounsfield Unit (HU) number of the SOS after reconstruction into 3-Dimension (3D) volume rendering (VR) image. Pearson's correlation coefficient test was used to determine relationship between the SOS and age for each gender using the two methods. Qualitative analysis showed a strong correlation in synchondrosis fusion stages and age for each gender (male, r = 0.885, p < 0.05 and female, r = 0.871, p < 0.05). Quantitative analysis using mean HU number generated by 3D VR also gives moderate and strong correlation for male (r = 0.672, p < 0.05) and female (r = 0.737, p < 0.05), respectively. Strong correlation of age with the SOS gives an overview and potential of utilizing the SOS for age estimation using both methods.